2018
DOI: 10.3892/etm.2018.5941
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-2 exhibits therapeutic benefits for osteonecrosis of the femoral head through induction of cartilage and bone cells

Abstract: Osteonecrosis of the femoral head is an orthopedic disease caused by femoral head damage or insufficient blood supply, which leads to the death of bone cells and bone marrow. Osteonecrosis of the femoral head leads to changes in the structure of the femoral head, femoral head collapse and joint dysfunction. Bone morphogenetic protein-2 (BMP-2) exhibits beneficial effects on bone formation, repair and angiogenesis at the femoral head. In the present study, the therapeutic effects of recombinant human BMP-2 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Kaback's [32] study showed that after the fracture model in mice was established, cartilage and tissue started to form after 7 days and sustained 10 days, meanwhile the mRNA level of Sox9 increased; Osterix was mainly expressed in the osteoblast near the site of fracture about 14 days later, meanwhile the expression of sox9 decreased, during this time cartilage became hard bone at the injured place. Numerous studies and clinical manifestations con rmed that BMP had unique osteogenic effect, and ber junction was completed at at 2 weeks' time after fracture [8,9] . The level of Osterix in BMP-2/Runx2/Osterix pathway appeared the lowest in group D (8-14 days), which was consistent with above study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaback's [32] study showed that after the fracture model in mice was established, cartilage and tissue started to form after 7 days and sustained 10 days, meanwhile the mRNA level of Sox9 increased; Osterix was mainly expressed in the osteoblast near the site of fracture about 14 days later, meanwhile the expression of sox9 decreased, during this time cartilage became hard bone at the injured place. Numerous studies and clinical manifestations con rmed that BMP had unique osteogenic effect, and ber junction was completed at at 2 weeks' time after fracture [8,9] . The level of Osterix in BMP-2/Runx2/Osterix pathway appeared the lowest in group D (8-14 days), which was consistent with above study.…”
Section: Discussionmentioning
confidence: 99%
“…PMOP is due to the rapid decline in estrogen levels in women after menopause and osteoclast resulting in a signi cant increase in bone resorption, while osteoblasts did not increase synchronously, resulting in bone resorption greater than bone formation, it's a metabolic disease [12] . The classical Wnt/β-catenin, BMP-2/Runx2/Osterix, OPG/RANKL and LGR4/RANKL/RANK signaling pathways play important roles in regulating osteogenesis and osteoclastogenesis [6][7][8][9][10][11] . Based on histological observation and molecular studies of fracture healing, the early stage of fracture healing is divided into early in ammatory response stage (within 1 days after fracture), non-speci c anabolic stage (within 3 days after fracture), non-speci c catabolism stage (3 days to 1 week after fracture) and more speci c anabolic stage of bone tissue ( 1week after fracture); while the typical fracture healing stage was divided into three stages: hematoma organization stage (2-3 weeks after fracture), original callus formation stage (4-6 weeks after fracture), callus reconstruction molding stage (more than 1 years after fracture) [13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGF-β signaling pathway plays a fundamental role in embryonic skeletal development and postnatal bone homeostasis [29]. Similar to other TGF-β family proteins, bone morphogenetic protein 2 (BMP-2) has been implicated in the pathogenesis of SONFH and has therapeutic bene ts for SONFH by inducing bone cells and cartilage [30]. The coupling of angiogenesis, dead bone absorption and new bone formation is a crucial link in the repair of femoral head necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the BMP family of proteins, including BMP-2, BMP-4 and BMP-7, have the potential to induce endochondral bone formation when implanted into mammals ( 11 ). BMP-2 has been previously demonstrated to be an osteoconductive growth factor beneficial for ONFH by promoting cartilage repair and inducing osteoblast proliferation or differentiation ( 12 ). Recombinant human BMP-2 (rhBMP-2) may improve the clinical efficacy of impacted bone graft surgery by enhancing bone repair in ONFH ( 13 ).…”
Section: Introductionmentioning
confidence: 99%